Behavioral Profiles of Clinically Referred Children with Intellectual Giftedness. (10th July 2013) - Guénolé, Fabian; Louis, Jacqueline; Creveuil, Christian; Baleyte, Jean-Marc; Montlahuc, Claire; Fourneret, Pierre; Revol, Olivier
Abstract : It is common that intellectually gifted children—that is, children with an IQ ≥ 130—are referred to paediatric or child neuropsychiatry clinics for socio-emotional problems and/or school underachievement or maladjustment. These clinically-referred children with intellectual giftedness are thought to typically display internalizing problems (i.e., self-focused problems reflecting overcontrol of emotion and behavior), and to be more behaviorally impaired when "highly" gifted (IQ ≥ 145) or displaying developmental asynchrony (i.e., a heterogeneous developmental pattern, reflected in a significant verbal-performance discrepancy on IQ tests). We tested all these assumptions in 143 clinically-referred gifted children aged 8 to 12, using Wechsler's intelligence profile and the Child Behavior Checklist. Compared to a normative sample, gifted children displayed increased behavioral problems in the whole symptomatic range. Internalizing problems did not predominate over externalizing ones (i.e., acted-out problems, reflecting undercontrol of emotion and behavior), revealing a symptomatic nature of behavioral syndromes more severe than expected. "Highly gifted" children did not display more behavioral problems than the "low gifted." Gifted children with a significant verbal-performance discrepancy displayed more externalizing problems and mixed behavioral syndromes than gifted children without such a discrepancy. These results suggest that developmental asynchrony matters when examining emotional and behavioral problems in gifted children.